2020
DOI: 10.1080/00268976.2020.1797918
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of astrophysically relevant ions in traps

Abstract: The detection of molecules in the interstellar medium relies on the comparison between observational and laboratory data recorded under relevant conditions. In this contribution, the use of cryogenic ion traps to obtain low temperature spectra of gas-phase ions of astrophysical relevance is reviewed. By exploiting the unique properties of these devices, the requisite spectroscopic data that led to the identification of C + 60 as the first carrier of the enigmatic diffuse interstellar bands could be measured. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 96 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…To address this, approaches involving nonstandard methods for synthesis combined with cooling, and action spectroscopy in cryogenic traps have been recently applied. 21 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this, approaches involving nonstandard methods for synthesis combined with cooling, and action spectroscopy in cryogenic traps have been recently applied. 21 …”
Section: Introductionmentioning
confidence: 99%
“…As a result, little spectroscopic data has been added to that compiled in the reviews in the 1990s by van Orden and Saykally, and Bowers and colleagues, in which this knowledge gap was highlighted. To address this, approaches involving nonstandard methods for synthesis combined with cooling, and action spectroscopy in cryogenic traps have been recently applied …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they found that the complexation of metals with fullerenes could lead to a far richer spectrum in the visible and near-infrared spectral range than fullerenes themselves, due to the charge transfer from the metal to the carbon cage, making them potential candidates for diffuse interstellar bands (DIBs). 59 The recent findings performed by Campbell et al , 60,61 about the synthesis of C 60 + ions tagged with helium and its UV-visible spectrum measurement, show experimental possibility that would support the speculations by Hou et al 19 about the charge transfer process of metallofullerenes and their contribution to the visible regime. Metals are widely known to be active catalysts for the synthetic production of various carbon nanostructures, including carbon cages under oxygen- and hydrogen-rich conditions as found by Dunk et al 38,41 Then, one may speculate from the study of Hou et al 19 that metal atoms and their ions might also play a catalytic role in fullerene formation in space, as metallofullerenes, if present, could be considered as byproducts of this catalytic process.…”
Section: Metallofullerenes In the Laboratorymentioning
confidence: 72%
“…Besides PAHs, buckminsterfullerene, C 60 , has also been identified in the ISM through its infrared bands using the Spitzer Space Telescope, 6 and this was confirmed through its electronic transitions in the far-red. 7,8 It is found that, close to stars, the abundance of C 60 increases rapidly while the abundance of PAHs decreases away from stars. 9,10 This has been attributed to photochemical fragmentation and isomerization processes under the influence of the strong stellar ultraviolet (UV) radiation field but the details of these processes are not yet understood.…”
Section: Introductionmentioning
confidence: 99%